A description of two new species of coccidia (Apicomplexa: Eimeriidae) from African reptiles with nomenclatural corrections for two Caryospora and one Eimeria species from snakes - Daszak, Peter; Ball, Stanley John (Folia Parasitologica)
Two new species of coccidian parasites are described from African reptiles. Oocysts of Eimeria foulshami sp. n. from the plated lizard Gerrhosaurus major bottegoi Del Prato of Sudan are ellipsoidal, 24.1 × 14.9 (23-26.5 × 14-17.8) µm with a bilayered, colourless oocyst wall and lack polar granules. The ellipsoidal sporocysts average 8.6 × 4.6 (7-10.6 × 4.4-7) µm and possess a prominent, globular, sporocyst residuum. Oocysts of Caryospora regentensis sp. n. from the green mamba Dendroaspis viridis Hallowell of Kenya are spherical to subspherical, 16.8 × 16.4 (16-17.6 × 15-17.2) µm with a bilayered oocyst wall and a single polar granule. The ellipsoidal sporocysts average 13.0 × 10.3 (10.2-14 × 9.2-11) µm and possess a Stieda and substieda body and a prominent globular sporocyst residuum. Oocysts of Caryospora legeri Hoare, 1933 are reported from a hissing sand snake, Psammophis sibilans sibilans L. from Nigeria, representing a new geographical record. The oocysts are slightly larger than the type, but otherwise identical. Caryospora psammophi Bray, 1960 and C. hermae Bray, 1960 from Psammophis sibilans phillipsi, oocysts of which are morphologically similar to and overlap in dimensions with C. legeri Hoare, 1933, are synonymised with the latter species. Eimeria samiae Iskander et Tadros, 1979 is emended to E. samyadeli to reflect the gender of the person the species was named after and because E. sami is preoccupied. In addition to these findings, Eimeria bohemi Modrý, Šlapeta et Koudela, 2000 and oocysts of an unidentified spherical Eimeria sp. are reported from Chamaeleo dilepis dilepis Leach from Cameroon.